Pengaruh Persepsi Harga, Kualitas Produk, dan Inovasi Produk terhadap Kepuasan Konsumen Kopi Jago di Jakarta Barat - Ricky Brian; Yugi Setyarko (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
This study aims to examine the effects of price perception, product quality, and product innovation on consumer satisfaction with Kopi Jago in West Jakarta. This study employed a quantitative approach. The population consisted of consumers who had purchased and consumed Kopi Jago products in the West Jakarta area. A total of 102 respondents were selected using a non-probability sampling technique with purposive sampling. The data were collected through questionnaires using a Likert scale. The study used quantitative data obtained through a survey method with questionnaires as the primary data collection instrument. The data were analyzed using IBM SPSS through multiple linear regression analysis. The results showed that price perception had a positive and significant effect on consumer satisfaction with Kopi Jago. Product quality also had a positive and significant effect on consumer satisfaction. Similarly, product innovation had a positive and significant effect on consumer satisfaction with Kopi Jago in West Jakarta. Therefore, the three independent variables—price perception, product quality, and product innovation—were found to have a significant effect on consumer satisfaction.